Implementing Trimatra Fine Arts Through Project-Based Learning In Inclusive Early Childhood Education - Pratiwi, Dewi; Amalia, Dina; Ratna, Endah Dwi (THUFULA, 2025)
The implementation of trimatra art learning in Early Childhood Education (ECE) has significant benefits for supporting child development, including stimulating motor skills, enhancing focus, and optimizing creativity. However, despite its advantages, the implementation of art education also encounters challenges that impact the achievement of learning objectives. This study explores the effectiveness of Project-Based Learning (PBL) methods in trimatra art for young children in Groups A and B at KB Inklusi Talenta, Kudus. This research employs a descriptive qualitative methodology, with a sample consisting of 20 children and 5 teachers from diverse backgrounds and varying special conditions. Data were collected through participatory observation, interviews with teachers, and documentation. The focus of the study is on how this method can be adapted to meet the needs of children with differing abilities and how it influences their engagement and learning outcomes. Challenges encountered include classroom management, project planning, and limited resources. The aim of this study is to identify the inhibiting factors in the implementation of project-based art learning and to provide recommendations for addressing these issues, facilitating broader adoption in inclusive ECE settings. Project-based learning in trimatra art activities has been shown to enhance children’s engagement and provide more meaningful learning experiences, making it an appealing approach in the context of inclusive education.